PENGARUH PENGETAHUAN DAN SIKAP TERHADAP PARTISIPASI MASYARAKAT PADA PENGELOLAAN BANK SAMPAH DI KECAMATAN BATU AJI – KOTA BATAM: Timbul Dompak dan Nikita Simarmata - Dialektika Publik (Prodi Ilmu Administrasi Negara, 2017)
This study aims to determine the effect of Knowledge (X1) and Attitude (X2) on Community Participation in Waste Bank Management (Y) in Batu Aji Sub-district, Batam City. This study uses a quantitative approach by distributing questionnaires to the garbage bank management unit located in Batu Aji district. This study used a saturated sample of 38 respondents. Data analysis used is multiple linear regression. The conclusions of the results of this study indicate that: (1). Partially that Knowledge influence to Community Participation in Waste Bank Management (t count = 5,736 > t table = 2,030); (2). Partially that Attitudes not affect Community Participation in Waste Bank Management (t count = 1.176 < t table = 2,030); (3). Simultaneously Knowledge and Attitudes significantly influence the Community Participation in Waste Management Bank (F count = 16.666> F table =3.27)